Pregunta
upstudy study bank question image url

Solve the equation by completing the square: \( z^{2}-4 z+20=3 \)

Ask by Hilton Chandler. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are \( z = 2 + i\sqrt{13} \) and \( z = 2 - i\sqrt{13} \).

Solución

We start with the equation:   z² - 4z + 20 = 3 Step 1. Bring all terms to one side:   z² - 4z + 20 - 3 = 0   z² - 4z + 17 = 0 Step 2. Isolate the quadratic and linear terms:   z² - 4z = -17 Step 3. Complete the square for z² - 4z. Take half of the coefficient of z: half of -4 is -2, and square it: (-2)² = 4. Add 4 to both sides:   z² - 4z + 4 = -17 + 4 Now, the left side can be written as a square:   (z - 2)² = -13 Step 4. Solve for z by taking the square root of both sides (remembering to include both ± solutions):   z - 2 = ±√(-13) Since √(-13) = i√13, we have:   z - 2 = ± i√13 Step 5. Solve for z:   z = 2 ± i√13 Thus, the solutions to the equation z² - 4z + 20 = 3 are:   z = 2 + i√13 and z = 2 - i√13

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the equation \( z^{2} - 4z + 20 = 3 \) by completing the square, first, let's rewrite it in standard form: 1. Subtract 3 from both sides: \[ z^{2} - 4z + 17 = 0 \] 2. Now, we focus on the quadratic expression \( z^{2} - 4z \). To complete the square, we take half of the coefficient of \( z \), which is \(-4\), giving us \(-2\). We then square this value: \[ (-2)^2 = 4 \] 3. Add and subtract this squared value inside the equation: \[ z^{2} - 4z + 4 - 4 + 17 = 0 \] This simplifies to: \[ (z - 2)^{2} + 13 = 0 \] 4. Now, isolate the square term: \[ (z - 2)^{2} = -13 \] 5. Since we can't take the square root of a negative number in the real number system, we introduce imaginary numbers: \[ z - 2 = \pm i\sqrt{13} \] 6. Finally, solving for \( z \): \[ z = 2 \pm i\sqrt{13} \] Thus, the solutions to the equation are \( z = 2 + i\sqrt{13} \) and \( z = 2 - i\sqrt{13} \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad